Changes in the position of the condyle after bilateral sagittal split ramus osteotomy in patients with mandibular retrusion and protrusion: a new condyle: fossa matching concept. Issue 10 (December 2019) - Yin, Q.; Bi, R.; Abotaleb, B.; Jiang, N.; Li, Y.; Zhu, S.
Abstract: The purpose of this study was to compare the condylar positional changes after bilateral sagittal split ramus osteotomy (BSSRO) in patients with mandibular retrusion and those with mandibular prognathism. We also studied the correlation between the degree of matching of the condyle and fossa, and condylar displacement. Thirty patients with mandibular retrusion (n = 11) or mandibular prognathism (n = 19) who underwent BSSRO were included. The condylar position was assessed from spiral computed tomographic (CT) scans taken preoperatively, during the first postoperative week, and at least 6 months postoperatively. All data were measured by MIMICS 17.0 and analyzed by Student's t test and Pearson's correlation analysis. The size of the condyles of patients with mandibular retrusion was significantly less than those of patients with mandibular prognathism (491.5 (172.8) compared with 823.2 (212.0) mm 3 ). The size of the glenoid fossa in those with mandibular retrusion (599.6 (110.4) mm 3 ) and those with prognathism (597.6 (151.6) mm 3 ) did not seem to differ. Postoperatively the condyles moved outwards, backwards, and downwards in both groups of patients. Correlation analysis between the condyle:fossa volume ratio and the condylar positional changes showed that a large condyle:fossa volume ratio correlated with the smaller positional changes in the condyle. The condylar position changed immediately after mandibular advancement and setback, and persisted in the long term. Larger condyles tended to have fewer positional changes.